(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: A common cause of adult nephrotic syndrome (NS) is membranous glomerulonephritis (MGN). The larger portion of MGN in adults is the idiopathic/ primary MGN (iMGN). So many conditions like autoimmunity, malignant tumor, drugs and infections can cause a secondary form of MGN. We can diagnose primary/ idiopathic MGN after the omission of all known secondary causes. As we know M-type phospholipase A2 receptor (PLA2R) on podocytes is the target antigen in the pathogenesis of primary MGN. Phospholipase A2 receptor (PLA2R) can be detected by immunohistochemically. Differences between primary MGN (iMGN) and secondary MGN are essential because of treatment implications. Objective: To evaluate the histopathological pattern of MGN and to correlate with PLA2R deposition in primary and secondary MGN in a group of Bangladeshi people. Methods: The research method is descriptive cross- sectional and observational. The study population was 60 patients in the department of Histopathology, AFIP, Dhaka Cantonment, Dhaka for duration of six months period from January 2019 to June 2019. At first, adequate clinical information was taken and categorized as primary and secondary MGN on a clinical basis, thereafter immuno- histochemistry of anti-PLA2R was done from formalin-fixed paraffin block of those cases. Results: A total of 60 diagnosed cases of MGN, 56 patients were found primary, and 04 were secondary based on clinical data. In my study, all primary MGN was found as PLA2R positive. Conclusion: The present study exhibits that immuno- histochemistry with anti-PLA2R antibodies can be the best diagnostic method for diagnosis of idiopathic MGN which offers an opportunity for personalized medicine. JAFMC Bangladesh, Vol 19, No 2 (December) 2023: 24-28